Hardware - Hard Work: Eine kritische Auseinandersetzung mit der Rolle von NGOs am Beispiel von unternehmenszentrierten Kampagnen in der ITK-Industrie - Bormann, Sarah (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2016)
In the past, anti-sweatshop campaigns have often focused on the apparel sector. More recently, these campaigns have broadened their spectrum as European NGOs increasingly begin to target technology companies producing smartphones and tablet computers, for example. This process comes with ambivalences, however: In the apparel sector, the importance of the local scale had been often unacknowledged. Within current campaigns targeting the ICT industries we can observe a decoupling of NGO driven activities on the consumer markets in the global north on one hand and labor struggles in the global south on the other. This does not only result in ineffective CSR-strategies, but it can also lead to a double victimization of female assembly line workers. The author discusses these contradictions and its implications for consumer focused tactics and coalitions between NGOs and trade unions. The article is based on the authors’ work with an NGO focusing on issues of labor in the ICT industry.